Pre-operative iron allows correction of anaemia before abdominal surgery: A systematic review and meta-analysis of randomized controlled trials. (28th May 2021) - Meyer, J; Cirocchi, R; Di Saverio, S; Ris, F; Wheeler, J; Davies, R J
Abstract: Objective: Professional surgical societies recommend the identification and treatment of pre-operative anaemia in patients scheduled for abdominal surgery. However, the evidence supporting this recommendation has been of poor quality until the recent release of several randomized controlled trials (RCT) addressing the question. Our aim was to determine if pre-operative iron allows correction of haemoglobin concentration and decreased incidence of peri-operative blood transfusion in patients undergoing major abdominal surgery. Methods: MEDLINE, Embase and CENTRAL were searched for RCTs written in English and assessing the effect of pre-operative iron on the incidence of peri-operative allogeneic blood transfusion in patients undergoing major abdominal surgery. Pooled relative risk (RR), risk difference (RD) and mean difference (MD) were obtained using models with random effects. Heterogeneity was assessed using the Q-test and quantified using the I2 value. Results: Four RCTs were retained for analysis out of 285 eligible articles. MD in haemoglobin concentration between patients with pre-operative iron and patients without pre-operative iron was of 0.81 g/dl (3 RCTs, 95% CI: 0.30 to 1.33, I2: 60%, p = 0.002). Pre-operative iron did not lead to reduction in the incidence of peri-operative blood transfusion in terms of RD (4 RCTs, RD: -0.13, 95% CI: -0.27 to 0.01, I2: 65%, p = 0.07) or RR (4 RCTs, RR: 0.57, 95% CI: 0.30 to 1.09, I2: 64%, p = 0.09). Conclusion: Pre-operative iron significantly increases haemoglobin concentration by 0.81 g/dl before abdominal surgery but does not reduce the need for peri-operative blood transfusion. Important heterogeneity exists between existing RCTs in terms of populations and interventions. Future trials should target patients suffering from iron-deficiency anaemia and assess the effect of intervention on anaemia-related complications.